Linking ethical leadership to employees' performance: Mediating role of organizational citizenship behavior and counterproductive work behavior - Arif Masih Khokhar; Muhammad Zia-ur-Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The scandals in recent years due to unethical behavior of leaders have shaken the confidence of stakeholders in public and corporate sectors. The scholars and practitioners are increasingly concerned about ethical issues related to business but still theoretical and empirical developments are lacking. The purpose of present study is to find the relationship of ethical leadership and employees' performance through mechanisms such as counterproductive work behavior and organizational citizenship behavior of employees. Drawing on social learning theory and social exchange theory, we propose that top management ethical leadership behavior (EL) contributes to employee's performance (EP) by enhancing organizational citizenship behavior (OCB) and reducing counterproductive work behavior (CWB). Sample to empirically test this framework includes participants such as principals, vice-principals, headmasters, and deputy headmasters of 107 educational institutions. Data were collected through questionnaires. Total questionnaires received were 237 out of 300 and 220 met the research criteria. The response rate was 79% out of which 90 were male and 130 were female participants. The results showed significant direct positive relationship between ethical leadership and employee's performance. Additionally, results showed that counterproductive work behavior (CWB) partially mediated the relationship between ethical leadership behavior and employee's performance. Interestingly, organizational citizenship behavior (OCB) did not mediate the relationship between ethical leadership and employees' performance. Present study will be a valuable addition to theory-based empirical research in the of field ethical leadership effectiveness. Theoretical and practical implications are also presented at the end.
Keywords: 330; ethical leadership (EL); organizational citizenship behavior (OCB); counterproductive work behavior (CWB); employees' performance (EP)